Lectotypification of 11 names of Eurya (Pentaphylacaceae) for the Flora of China - Ji, Chun-Feng; Zhang, Li-Bing (Phytotaxa, 2016)
Eurya Thunberg (1783: 67) is a genus of Pentaphylacaceae and it contains about 130 species distributed widely in tropical and subtropical Asia and the Pacific Islands; 83 species (63 endemic) are known from China (Ming & Bartholomew 2007). The genus was assigned to Theaceae in FRPS (Ling, 1966), while molecular studies (e.g., Tsou & Vijayan, 2016) placed it in Pentaphylacaceae and resolved it as a monophyletic group which is recognized here. Notably, paraphyletic groups are sometimes advocated by some authors (e.g., Brummitt, 2014; Ehrendorfer & Barfuss, 2014; George, 2014; Hörandl, 2014; Stuessy & Hörandl, 2014; Stuessy et al., 2014). Species of Eurya often have unisexual flowers. In an effort to update the online version of Flora of China (www.efloras.org/flora_page.aspx?flora_id=2), we found that two gatherings were designated as types for each of 11 names of Eurya published in a same article by Chang (1954). Here we lectotypify these 11 names by choosing one of the two gatherings designated as the lectotype of each name so that the application of these names can be stabilized.